2018
DOI: 10.1016/j.jeap.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

"I'm nobody's Mum in this university": The gendering of work around student writing in UK higher education

Abstract: A number of recent studies have raised critical questions about the gendering of academic labour in the contemporary university as workplace. This paper focuses on gendering discourses of work around student writing which surfaced in an ethnographically oriented study of fourteen academic teacher participants based in six diverse UK Universities in a range of disciplines. I draw on study findings to show that work with undergraduate writing and writers is often understood through feminising discourses of 'care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Another favourite theme concerns academic socialization given the special attention that academic literacies practitioners dedicate to students and their conflicting relationship with academia, torn as they are between desire and (self)distrust. Not just the students receive attention and care, also other participants in need of support become the privileged interlocutors of academic literacies teacher-researchers: for example, other teachers struggling under the unfair distribution of academic work and burdened by students' emotional and cognitive demands (Tuck, 2018); tutors usually relegated to the role of "language fixers", who can instead promote awareness of "societal linguistic discrimination" in their students (Helmer, 2013, p. 281); trans scholars and activists usually marginalized in academia and claiming visibility through fair citation practices (Thieme & Saunders, 2018).…”
Section: An Overview Of Academic Literaciesmentioning
confidence: 99%
“…Another favourite theme concerns academic socialization given the special attention that academic literacies practitioners dedicate to students and their conflicting relationship with academia, torn as they are between desire and (self)distrust. Not just the students receive attention and care, also other participants in need of support become the privileged interlocutors of academic literacies teacher-researchers: for example, other teachers struggling under the unfair distribution of academic work and burdened by students' emotional and cognitive demands (Tuck, 2018); tutors usually relegated to the role of "language fixers", who can instead promote awareness of "societal linguistic discrimination" in their students (Helmer, 2013, p. 281); trans scholars and activists usually marginalized in academia and claiming visibility through fair citation practices (Thieme & Saunders, 2018).…”
Section: An Overview Of Academic Literaciesmentioning
confidence: 99%
“…Many of our female colleagues carry greater teaching hours than their male peers and are asked to organise and manage social events such as Open Day and student orientation because they are ‘nicer or more approachable’. These gendered expectations of female academics’ pastoral care endure in both student and institutional eyes (Ashencaen Crabtree & Shiel, 2019; Tuck, 2018). Thus, female academics experience ‘obscured service burdens’ (Docka-Filipek & Stone, 2021) since academic housework jobs are unequally distributed to women over male colleagues (Heijstra et al, 2017).…”
Section: Gendered Constraints In the Academic Career Journeymentioning
confidence: 99%
“…However, a number of studies have shown that citation practices are far from neutral and tend to reproduce a range of hierarchical relations, including male/female hierarchies. Quantitative research has been able to show that female scholars are underrepresented in citation counts (Davenport & Snyder, 1995); that even when other factors are equal, male faculty have a higher likelihood to be highly cited (Toutkoushian, 1994); that where raw publication counts are equal, women across the natural sciences, social sciences, and humanities are less likely to be in the prestigious first author position (West, Jacquet, King, Correll, & Bergstrom, 2013); and that as citations of women's publications increase, this increase tends to occur within articles by other women with male scholars not citing women at the increased rate in which they have entered a field (Lutz, 1990;McElhinny, Hols, Holtzkener, Unger, & Hicks, 2003;see Nygaard and Bahgat, 2018). Much as they are able to reveal about gendered patterns of citation, such studies bear the flaw that they base their quantitative work on a stable and exclusively binary model of gender identity, working with the assumption that authors are neatly dividable into male and female categories, even as ambiguities in the use of first names and initials are noted.…”
Section: The Research Article Citation and Gendermentioning
confidence: 99%